2017
DOI: 10.1159/000479111
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences of Nonmotor Symptoms Affecting Quality of Life in Parkinson Disease

Abstract: Background/Aims: Gender differences of health-related quality of life (HRQoL) in patients with various disorders have been reported. Various nonmotor symptoms (NMSs) also affect the patients' lives and HRQoL, even in the early stages of Parkinson disease (PD). Our study aimed to identify whether there are gender differences of HRQoL in PD patients in the early stages, and which NMSs are associated with HRQoL depending on gender. Method: Eighty-nine PD patients (47 males, 42 females) and 36 healthy controls wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 25 publications
1
26
2
Order By: Relevance
“…In total, 5950 studies were identified in target databases and 2 other studies were retrieved from reference lists. The final sample included in the meta‐analysis consisted of 20 studies with 2707 PD patients and 150,661 healthy controls 8,9,13,27‐41 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 5950 studies were identified in target databases and 2 other studies were retrieved from reference lists. The final sample included in the meta‐analysis consisted of 20 studies with 2707 PD patients and 150,661 healthy controls 8,9,13,27‐41 …”
Section: Resultsmentioning
confidence: 99%
“…Four studies applied PDQ‐39 13,30,41,55 and all of them had available data and were included in the meta‐analysis. Other QOL measures were also used such as the generic 15D questionnaire (15D), 56 the Health Utilities Index Mark 3 (HUI3), 57 Nottingham Health Profile (NHP), 58,59 the Life Satisfaction Questionnaire (LiSat‐11), 60 an item of the International Prostate Symptom Score (IPSS) 61 and a newly developed QOL questionnaire 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, female PD patients showed lower QOL than male patients. The sex differences in nonmotor symptoms have been widely investigated [18], and it has been considered that socioeconomic status, occupational functioning, and hormonal differences between the sexes could contribute to these differences. This finding is in line with current published evidence that practitioners should be concerned with managing nonmotor symptoms as well as motor symptoms in de novo PD patients [19].…”
Section: Discussionmentioning
confidence: 99%
“…Over all, further studies on a large number of patients and long follow up are needed to determine the impact of DBS on QOL taking into account both motor and non-motor symptoms. The moderate improvement of QOL by STN DBS reported up to now highlights the major influence of nonmotor symptoms on quality of life ( 67 , 68 ).…”
Section: Discussionmentioning
confidence: 94%